Design of uncertain displacement controlled velocity control system for hydraulic actuator - Jabbar H. Mohmmed; Ahmed K. Hassan; Muslim Ali; Samer A. Kokz; Muhanad Hamed Mosa; A.K. Kareem; Ahmed A. Zainulabdeen; Z.C. Feng (Heliyon, 2024)
Displacement-controlled systems have high efficiency and are widely used in industry. Accurate control of the actuator motion in hydraulic systems is usually a necessity in industrial applications such as the motion of control surfaces in fixed-wing airplanes for flight control as well as the aircraft brake systems. To address this need, the current study was conducted with the goal of developing a high-fidelity model to achieve precise control. This work focused on modeling a hydrostatic transmission that is used for controlling a linear actuator velocity. The flow entering the actuator was changed using a variable displacement pump. The study included examining the stability and performance of the open-loop system. Additionally, the study involved the design of the proportional-integral-derivative PID and H∞ controllers, followed by the analysis of the stability and performance of the closed-loop system with both controllers. Furthermore, the multiplicative uncertainty is taken into account and the robustness of the system is verified using controllers PID and H∞. In the current study,Uncertain parameters such as actuator efficiency, pump speed, and viscous friction coefficient were considered and allowed for a ±5% deviation from their stated values. Taking uncertainty into account ensures that the system performs properly even in case where the design parameters vary within the specified range. The system response is compared for the cases of open-loop system, closed-loop system with PID controller, and closed-loop system with H∞ controller. The results demonstrated that the open-loop system remains stable for real-world applications but shows insufficient performance in terms of input tracking and disturbance rejection. The introduction of the PID controller significantly enhanced the system's response to a reference input; however, its disturbance rejection capabilities in terms of overshoot and settling time were still unsatisfactory. The system equipped with the PID controller failed to meet the robustness requirements. Conversely, the utilization of H∞ controllers yielded superior responses and fulfilled the robustness criteria.